CORRECTION OF CLINICAL AND FUNCTIONAL CHANGES IN THE KIDNEYS WITH INFLUENCE ON THE STRUCTURAL AND FUNCTIONAL STATE OF THE VESSELS AND, ON THIS BASIS, ASSESSMENT OF THE DEVELOPMENT OF CHRONIC KIDNEY DISEASE - Botir T. Daminov; Umidjon X. Sobirov (Central Asian Journal of Medicine, 2025)
The article reflects the results of studies conducted in 101 patients in the conservative stage of chronic kidney disease to assess structural and functional changes in blood vessels and improve the clinical and functional state of the kidneys with the use of hypotensive and angioprotective drugs, as well as to assess the progression of renal failure. In this case, the level of exacerbation of chronic kidney disease based on various treatment regimens is substantiated by accurate statistical calculations. At the same time, opinions and considerations are presented on various areas of future prospective research that should be carried out for the further improvement of the industry.